(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2022)
The study of artificial caves and underground complexes, as well as their protection and preservation, remains a pressing problem of modern scientific research. Ancient dungeons, which are located not only in the territories of major cities (mainly in places where there were castle fortifications, trading rows, and monasteries), but also in small towns, cities, and villages, are in unsatisfactory condition. The work is devoted to the analysis of cave complexes and underground premises for historical purposes. Special attention should be paid to the operating conditions. The methods of surveying underground premises are given, in particular, attention is paid to the creation of 3D models. The results of the study of brick on water absorption result. The article pays attention to methods of strengthening damaged structures in operation conditions with modern composite materials based on basalt and carbon fibers